The Relationship of Reading Interest with Learning Outcomes in Class IX MTS Students' Civics Subjects Single Islamic Academic Year 2017/2018 - Pratiwi, Erni; Amin, Zulkifli (Lembaga Riset Mutiara Akbar, 2022)
The problem of this research is whether there is a relationship between reading interest and student learning outcomes in citizenship education subjects at MTs. Islamiyah Sunggal in the 2017/2018 academic year. The purpose of this study was to determine the relationship between reading interest and student learning outcomes in citizenship education subjects at MTs. Islamiyah Sunggal in the 2017/2018 academic year. The population used in this study was class IX at MTs. Islamiyah Sunggal Medan which consisted of 4 classes with a total of 129 students. The sampling technique in this study used purposive sampling, namely the class that was the sample studied was class IX with 30 students. The instrument used is a closed questionnaire. In which this questionnaire conducted observations at MTs. Islamiyah Sunggal Medan and a questionnaire on the Relationship of Reading Interest with Student Learning Outcomes. From the results of this study, it can be seen that there is an increase in student learning outcomes with the relationship between reading interest and the research conducted, it is found that the relationship between reading interest is very influential on student learning outcomes in the subject of Citizenship Education. This is evidenced by the value of the correlation coefficient r?count = 1.094. From table r Product Moment for N = 30 obtained rtable = 0.361. So, because (1.094) > (0.361) then the correlation is very strong. From the results of the calculation of the hypothesis obtained t?itung = 13.075 with a significant level = 0.05 and dk = n – 2 = 30 – 2 = 28, then get the price = 1.701. Obtained t?itung13.075> 1.701. This means that Ha is accepted, meaning that there is a significant influence between the relationship between reading interest and student learning outcomes. Thus, it is concluded that there is a relationship between reading interest and student learning outcomes in civic education subjects at MTs. Islamiyah Sunggal Medan in the 2017/2018 academic year